The Covid-19 Vaccination’s Obligation in Pandemic Era Relates to Autonomous Rights and Informed Consent - Nila Nirmalasari; Helmi Helmi; Mirza Satria Buana; Nasrullah Nasrullah (Hang Tuah Law Journal, 2022)
The government requires the Covid-19 vaccination in a pandemic emergency to reduce and stop the spread of this virus. Based on the study of several previous studies, this mandatory vaccination program received a great reaction in the community, not only in Indonesia, there were those who supported it and there were those who opposed it This paper aims to examine the obligation of Covid-19 vaccination with autonomous rights and informed consent. This research was conducted using a normative legal research method, with a statute and a conceptual approach. The research results are vaccination is part of health care efforts. Informed consent is obligation in every health care efforts. The Covid-19 Vaccination is also obligation in pandemic era. The mandatory Covid-19 vaccination program can be justified because the country is in a pandemic emergency. My advice in terms of respecting the right to autonomy, every act of Covid-19 vaccination should be accompanied by informed consent, either in an implied or written form, even though this program is a mandatory program.